LEARNING MEDIA DEVELOPMENT DORAEMON'S TEAMS (TEAMS GIFT) FOR ELEMENTARY SCHOOL THEMATIC LEARNING - Dwi Nurul Hayati; Minto Santoso; Sripit Widiastuti (JOSAR (Journal of Students Academic Research), 2019)
Based on field observations, students need media that can improve motivation and easy to use during the learning process so that it is expected to be able to improve student learning performance.The purpose of this research is to explain the development of media, expose the use of media, and explain the improvement of learning performance with teams ' gift learning media in thematic learning in elementary schools.This research is a research and Development (R&D) conducted using the Borg and Gall (Sugiyono,2016) model modified according to the needs of researchers. The subject of this study is a class II student UPT SD Negeri Kedawung 01. The results show that, media assessments by media experts and material experts are each 76% and 83% respectively, teams ' gift media has 4 game stages which are Group division stage, learning stage, and gift division level, and response The use of media by learners of 86% as well as student learning achievements increased from an average value of 74.04 to 88.85 with N-Gain counting results showing a score of 0.5639 in a medium category. Teams ' gift learning Media is worth testing on the field and can improve student learning achievements.